Potential use of BIM for automated updating of building materials values - Jacoski, Claudio Alcides; Machado Hoffmeister, Lissandro (Brazilian Journal of Operations & Production Management, 2018)
This study proposes an artifact motivated by improved assertiveness in building design budgets. Building Information Modeling (BIM), with the structure of the parametric objects created in a file format with the Industry Foundation Classes (IFC) extension, can provide the data for the object, facilitating the design’s control and monitoring process. Through the adoption of the IFC standard in the creation of these objects, the exchange of information between the tools of different software providers becomes viable, allowing interoperability between systems. This is a desired situation in the construction industry, which incurs significant losses due to this problem. An important condition that can significantly contribute to the update of the information of the objects and the budget process is the incorporation of the possibility of updating the value information (price) of the BIM objects that are shared in repositories (object libraries). In this context, this study presents an alternative to updating and retrieving the values of BIM objects based on the IFC standard. An artifact (web environment) was produced linked to a model to meet the proposed objective. This method is presented by computing services, enabling the automated retrieval of the object value between the owners, the price repository and also the designers. The performed tests reveal the practicality of its implementation, with no extensive knowledge of the IFC structure being necessary. It suffices to simply follow the fill out pattern of the custom properties in IFC, defined during the creation of the object. The submission of the construction design to the repository allows for the retrieval of the values and the quantification of objects present in the design. This process is carried out in a simple manner, maintaining the synchrony and traceability of the object with the designer and the owners of the objects making up the architectural and complementary design.